2015
DOI: 10.1016/j.molp.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

A Gene Expression Profiling of Early Rice Stamen Development that Reveals Inhibition of Photosynthetic Genes by OsMADS58

Abstract: Stamen is a unique plant organ wherein germ cells or microsporocytes that commit to meiosis are initiated from somatic cells during its early developmental process. While genes determining stamen identity are known according to the ABC model of floral development, little information is available on how these genes affect germ cell initiation. By using the Affymetrix GeneChip Rice Genome Array to assess 51 279 transcripts, we established a dynamic gene expression profile (GEP) of the early developmental process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 106 publications
3
42
0
1
Order By: Relevance
“…S5; Chen et al, 2015b) showed that BR biosynthesis-and signaling-related genes display nonuniform expression patterns (Fig. 6A).…”
Section: Vital Roles Of Phytohormones In Lamina Joint Developmentmentioning
confidence: 99%
“…S5; Chen et al, 2015b) showed that BR biosynthesis-and signaling-related genes display nonuniform expression patterns (Fig. 6A).…”
Section: Vital Roles Of Phytohormones In Lamina Joint Developmentmentioning
confidence: 99%
“…If the induction of archesporial cells requires a hypoxia condition as indicated by Kelliher and Walbot (2012), there must be a mechanism to create a proper microenvironment for germ cell initiation. The Arabidopsis anther has well-differentiated chloroplasts (Chen et al, 2015) and is thought to be photosynthetically active; thus, the anthers would constantly release oxygen. If this is the case, it is reasonable to hypothesize that MPK3/6 may play a role in early stamen development in Arabidopsis, responding to the oxidative status and stabilizing the SPL protein via phosphorylation to ensure germ cell formation.…”
Section: Mpk3/6 May Mediate Environmental Stress Signals For Dgc Indumentioning
confidence: 99%
“…These studies yielded a comprehensive view of gene expression during flower formation. However, because the available data did not always provide detailed information on when and where genes are expressed, additional studies conducted in recent years have aimed at increasing the spatio-temporal resolution of the gene expression map for flower development (Jiao and Meyerowitz, 2010;Wuest et al, 2010;Mantegazza et al, 2014;Chen et al, 2015;Ryan et al, 2015;Villarino et al, 2016). To this end, a wide range of methods, such as laser capture microdissection Mantegazza et al, 2014) or fluorescence-activated cell sorting, in combination with a flower synchronization system Villarino et al, 2016), was used.…”
Section: Genes Involved In Floral Organogenesismentioning
confidence: 99%